2019
DOI: 10.1016/j.devcel.2019.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Organ Growth Coordination Is Mediated by the Xrp1-Dilp8 Axis in Drosophila

Abstract: How organs scale with other body parts is not mechanistically understood. We have addressed this question using the Drosophila imaginal disc model. When growth of one disc domain is perturbed, other parts of the disc and other discs slow down their growth, maintaining proper inter-disc and intra-disc proportions. We show here that the relaxin-like Dilp8 is required for this inter-organ coordination. Our work also reveals that the stress-response transcription factor Xrp1 plays a key role upstream of dilp8 in l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 37 publications
5
85
0
1
Order By: Relevance
“…Here we provided evidences that JNK coordinates intra-organ growth in a Jun/Fos-dependent manner through a mechanism involving expression of Dilp8 and generation of ROS, two different signaling events that independently regulate tissue size and cell number. Dilp8 has been recently identified as a signaling molecule produced by damaged imaginal discs able to delay metamorphosis and systemically reduce growth [39,40,57]. In developing wing discs, we have showed that Dilp8 expression in slow growing cell populations contribute to size reduction of adjacent wild-type territories, thereby contributing to organ proportion maintenance.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Here we provided evidences that JNK coordinates intra-organ growth in a Jun/Fos-dependent manner through a mechanism involving expression of Dilp8 and generation of ROS, two different signaling events that independently regulate tissue size and cell number. Dilp8 has been recently identified as a signaling molecule produced by damaged imaginal discs able to delay metamorphosis and systemically reduce growth [39,40,57]. In developing wing discs, we have showed that Dilp8 expression in slow growing cell populations contribute to size reduction of adjacent wild-type territories, thereby contributing to organ proportion maintenance.…”
Section: Discussionmentioning
confidence: 74%
“…Interestingly, when activation of JNK pathway was reduced, either by using Dilp8 is required to coordinate intra-organ growth downstream of Eiger/JNK signaling Recently, Drosophila insulin-like peptide 8 (Dilp8) has been identified as a signaling molecule produced by imaginal discs in response to tissue damage [39,40]. Dilp8 production by slow growing or damaged tissues results in activation of neuronal receptor Lgr3 which in turn downregulates ecdysone synthesis therefore delaying metamorphosis and systemically reducing growth [39][40][41][42][43]. Interestingly, we observed a strong induction of dilp8 transcript levels upon RA CS or dmyc RNAi expression ( Figure 5A, Figure S1 and Table S1).…”
Section: Eiger-induced Jnk Signaling Is Required For Non-cell-autonommentioning
confidence: 99%
“…Finally, we show that similarly to what was previously described for Ras signaling (Atkins et al, 2016), the cooperation between Notch signaling and polarity loss is controlled by a “tumor transcriptional network” centered around the AP-1/Stat/Yki transcription factors, and including the critical bZIP factors Pdp1 and CEPBG (CG6272/Irbp18). But our analysis uncovered a previously unreported role for the cell competition regulator, and Irbp18 binding partner Xrp1 (Baillon et al, 2018; Blanco et al, 2020; Boulan et al, 2019; Ji et al, 2019), raising the interesting prospect that neoplastic growth could be mediated at least in part, by co-opting cell competition.…”
Section: Discussionmentioning
confidence: 80%
“…This would align with the NS specific GO categories “cellular response to gamma radiation” (GO:0071480), and “DNA damage checkpoints” (GO:0031571/0007095). Indeed, Xrp1 has recently been linked to cell competition and shown to control the expression of a subset of genes activated in response to Ribosomal protein haplo-insufficiency including Ets21C , upd3 , or ilp8 in developing wing discs (Baillon et al, 2018; Boulan et al, 2019; Ji et al, 2019). Strikingly, we observed a very strong overlap between the Xrp1 transcriptional program (Supplemental Table S16) and the genes activated in NS (60 out of the 171 Xrp1 positively regulated genes are also upregulated in NS; hypergeometric test, p=4.71 10e-21), while a much more modest overlap could be observed with N or S (overlap of 17 and 33 with p values of 1.12 10e-3 and 1.56 10e-8 respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Mallik et al recently reported that neuronal dysfunction in caz loss-of-function mutants is mediated by increased expression of Xrp1 [10], a DNA-binding protein involved in protection against genotoxic stress [17], DNA damage repair [18], cell competition [19,20] and intra-and inter-organ growth coordination [21]. Increased Xrp1 expression in caz mutant central nervous system led to gene expression dysregulation and neuronal dysfunction [10].…”
Section: Discussionmentioning
confidence: 99%